2009
DOI: 10.1016/j.polymer.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Au and Au–Pt nanoparticles within PMMA matrix using UV and X-ray irradiation

Abstract: a b s t r a c tAu and Au-Pt alloy nanoparticles are prepared and patterned at room temperature within the PMMA polymer matrix by the action of 254 nm UV light or X-rays. The polymer matrix enables us to entangle the kinetics of the photochemical reduction from the nucleation and growth processes, when monitored by UV-vis spectroscopy. Accordingly, increase of the temperature to 50 C of the reaction medium increases the nucleation and growth rates of the nanoparticle formation by more than one order of magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
0
34
0
1
Order By: Relevance
“…25 Together with further contributions from Ozkaraoglu 35 et al, Karadas and co-workers showed that the disappearance of Au 3+ peaks in the XPS spectra occur via first-order kinetics but at differing rates. [27][28] In view of this, the content of Au 3+ obtained by XPS always lower than those obtained by TPR is reasonable.…”
Section: Resultsmentioning
confidence: 51%
“…25 Together with further contributions from Ozkaraoglu 35 et al, Karadas and co-workers showed that the disappearance of Au 3+ peaks in the XPS spectra occur via first-order kinetics but at differing rates. [27][28] In view of this, the content of Au 3+ obtained by XPS always lower than those obtained by TPR is reasonable.…”
Section: Resultsmentioning
confidence: 51%
“…Polymer-inorganic oxide nanoparticle composites have attracted considerable attention in the field of material science because they exhibit enhanced material properties as compared to pure polymers. The presence of inorganic oxide nanoparticle fillers in polymers can alter the thermomechanical, optical, electrical, and magnetic properties of the polymers [4]. Recently, composite materials made of polymers and nanoparticles (NPs), such as inorganic, metal, semiconductor, carbon black, and magnetic nanomaterials have attracted great attention because of the stabilizing effects of the polymer matrix on the NPs and relative easiness and flexibility of engineering this class of materials with advanced functionalities [4]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-materials were attracted the interesting of many researchers due to their physical and chemical properties as well as their applications in different fields [1]- [4]. Also, composite materials from polymers and nanoparticles (NPs) have advanced applications in the field of material science [5]- [7].…”
Section: Introductionmentioning
confidence: 99%